Support for agricultural policy-making in sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Improving agricultural policy-making at the national level constitutes a major challenge for all those concerned with agricultural development in Africa. It is common knowledge that a strong information base is a prerequisite for sound policy making...